Principles of Flexible Endoscopy for Surgeons - Marks, Jeffrey M.; Dunkin, Brian J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Written entirely by surgical endoscopists, Principles of Flexible Endoscopy for Surgeons presents a comprehensive overview of past, present, and future flexible gastrointestinal endoscopic techniques, with a focus on educating surgeons who may or may not already have the skills to perform flexible endoscopy. In addition to the endoscopic management of surgical issues, the volume describes the role of surgery in the management of endoscopic complications. Basic as well as advanced flexible endoscopic techniques are presented in both a didactic and visual mode, with representative endoscopic images and video clips. Recent endoscopic advancements which are not routinely a core component of surgical training programs are also covered in detail. Extensively illustrated with endoscopic images and accompanied by a DVD, Principles of Flexible Endoscopy for Surgeons is a valuable resource for surgeons on all facets of flexible endoscopy.
A History of Flexible Gastrointestinal Endoscopy -- Basic components of flexible endoscopes -- Setup and care of endoscopes -- Pre-procedural Considerations -- Intraoperative considerations -- Post-procedural considerations -- Endoscopic tools/techniques for tissue sampling -- Tools and Techniques for Gastrointestinal Hemostasis -- Endoscopic Tools and techniques for Tissue Removal and Ablation -- Endoscopic Tools and techniques for strictures and stenoses -- Endoscopic techniques for enteral access -- Endoscopic tools and techniques for fistula and leaks -- Endoscopic considerations in morbid obesity -- Endoscopic considerations in Gastroesophageal Reflux Disease (GERD) -- Intraoperative Endoscopy -- Techniques of upper endoscopy -- Techniques and tips for lower endoscopy -- Techniques of office based endoscopy: Unsedated Transnasal Endoscopy -- Techniques of Endoscopic Retrograde Cholangiopancreatography -- Management of endoscopic complications -- Photodocumentation of endoscopic findings -- Future of endoscopy.
Keywords: Medicine; Gastroenterology; Surgery; Endoscopic surgery; Medicine & Public Health; General Surgery; Minimally Invasive Surgery; Gastroenterology